2021
DOI: 10.1080/10717544.2021.1921075
|View full text |Cite
|
Sign up to set email alerts
|

A novel dendritic mesoporous silica based sustained hydrogen sulfide donor for the alleviation of adjuvant-induced inflammation in rats

Abstract: Purpose S-propargyl-cysteine (SPRC), an excellent endogenous hydrogen sulfide (H 2 S) donor, could elevate H 2 S levels via the cystathionine γ-lyase ( CSE)/H 2 S pathway both in vitro and in vivo . However, the immediate release of H 2 S in vivo and daily administration of SPRC potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Our previous study used SPRC with dosage of 100 mg kg −1 for the treatment of AIA in rats through subcutaneous injection or oral administration once q72h, which showed gratifying therapeutical effect, while the dosage of 50 mg kg −1 showed limited therapeutical effect. 55,58 However, in this study, we have different findings. In the SPRC group, we solely used SPRC at dosage of 50 mg kg −1 , consistent with our previous studies, there was no treatment effects could be observed.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our previous study used SPRC with dosage of 100 mg kg −1 for the treatment of AIA in rats through subcutaneous injection or oral administration once q72h, which showed gratifying therapeutical effect, while the dosage of 50 mg kg −1 showed limited therapeutical effect. 55,58 However, in this study, we have different findings. In the SPRC group, we solely used SPRC at dosage of 50 mg kg −1 , consistent with our previous studies, there was no treatment effects could be observed.…”
Section: Discussionmentioning
confidence: 64%
“…The reason for the improved therapeutical effect was possibly through two aspects, for one aspect, the sustained release of SPRC from SK@MS might elevate the H 2 S concentration in vivo in a relevant stable level compared with SPRC powder. 58 , 69 For another aspect, the co-deliver of NSAIDs might also augment the therapeutical potency of SPRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…463 SPRC might serve as a potential drug for RA treatment. We have developed two sustained-release donors of hydrogen sulfide, 464,465 which has solved the problem of hydrogen sulfide release too fast in conventional formulations. ZYZ-802 is filing for clinical trials by CFDA and FDA now.…”
Section: Drugs In Clinical Trialsmentioning
confidence: 99%
“…The current effect of H 2 S-delivered nanomaterials for the treatment of diseases is mainly immunomodulatory or anti-inflammatory. Yu et al demonstrated a solution to the problem of premature release of the H 2 S donor S-propargylcysteine using polylactic acid (PLA) microspheres and dendritic mesoporous silica nanoparticles, achieved a slow release of H 2 S in vivo for up to 3 days, and observed improved adjuvant-induced arthritis scores, inflammatory factor indices, and imaging performance in rats [ 137 , 138 ]. S-Propargylcysteine exerts antioxidant effects through the upregulation of the Nrf2-antioxidant response element (ARE) signaling pathway, and its use in treating RA is well established [ 139 ].…”
Section: H 2 Smentioning
confidence: 99%